2017
DOI: 10.1515/msac-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Clay Ceramic Filter for Water Treatment

Abstract: -Ceramic water filters were prepared from different proportions of kaolin and soft wood and sintered at 900 °C, 950 °C, and 1000 °C. The flow rate, conductivity, pH of filtered water and removal efficiency (microbial, water hardness agent's, nitrite and turbidity) were analysed. The ceramic filter with 15 % saw dust, 80 % clay and 5 % grog that was fired at temperature of 950 °C or 1000 °C showed the best removal efficiency. Statistical ANOVA tests showed a significant difference between ceramic filters with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…Ceramic water filtration is the process of passing water through a porous ceramic material. It is a promising way to reduce the burden of water-borne diseases; it is affordable in terms of cost and made from local resources [2]. It has been shown that ceramic filters can reduce turbidity [3] and microorganism [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramic water filtration is the process of passing water through a porous ceramic material. It is a promising way to reduce the burden of water-borne diseases; it is affordable in terms of cost and made from local resources [2]. It has been shown that ceramic filters can reduce turbidity [3] and microorganism [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is a promising way to reduce the burden of water-borne diseases; it is affordable in terms of cost and made from local resources [2]. It has been shown that ceramic filters can reduce turbidity [3] and microorganism [2]. Meanwhile, physico-chemical properties of ceramic filters such as porosity and chemical stability are important to evaluate the filter efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The ceramic filter with 15 % saw dust, 80 % clay and 5 % grog that was fired at temperature of 950 °C or 1000 °C showed the best removal efficiency. Statistical ANOVA tests showed a significant difference between ceramic filters with various compositions in their removal efficiencies [10].…”
Section: Introductionmentioning
confidence: 98%
“…A mixture of the most effective and stable is a pottery strainer rice husk mixture with the composition of the main ingredients of clay and rice husk 80% and 20% [12]. The ceramic filter with 15 % saw dust, 80 % clay and 5 % grog that was fired at temperature of 950 °C or 1000 °C showed the best removal efficiency [10]. Tests showed that copper is a suitable antibacterial agent to combat coliforms in contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2018, andJassim, et., al., 2013). Its properties can be controlled by developing technology to meet certain purposes (Zereffa, Bekalo, 2017) . The pore size of the ceramic material can be made homogeneous and small within the range of microfiltration ( Jassim, 2010), which is excellent to remove most of the suspended solids and bacteria (Nurmiyanto, Prasetya, 2012).…”
Section: Introductionmentioning
confidence: 99%